Use of Dental Implants and Micro-Implants in Orthodontic Treatment of Dental Patients - Bobokal А. М. (Actual Dentistry, 2025)
Relevance. Anchors (stable supports) are one of the most essential components of successful orthodontic treatment. Traditionally, orthodontics uses teeth and extra- or intraoral appliances for retention, and their effectiveness often depends on the patient’s willingness. Micro-implants (OMI) in orthodontics are called temporary anchor devices (TADs) or mini-implants. Or mini-screws are used to perform complex orthodontic movements. Orthodontic mini-implants can be an effective adjunct in resolving complex displacements. Aim: analyze the literature and assess the frequency of rejection and factors affecting the stability and success of temporary anchorage devices (TADs) used as orthodontic retainers. Material and methods. Data were collected from electronic databases PubMed and Google Scholar. The following inclusion criteria were used to select eligible articles: English-language articles containing prospective and retrospective clinical and experimental studies of implants and screws used as orthodontic retention devices. The search yielded 209 abstracts on TADs used as anchors. After reviewing and applying the selection criteria, 66 articles were included in the study. The data obtained was divided into two themes: factors that influenced the success rate of TADs, and to what extent and in how many papers these factors were cited. Clinical characteristics were divided into three main groups: patient-related, implant-related, and treatment-related. Although all papers included in this literature review reported success rates of 80% or higher, the factors determining success rates were inconsistent across all studies reviewed, making it difficult to draw any conclusions. Results. The overall success rate of skeletal fixation with micro-implants was 79%. The success rate was independent of gender, age, and side of placement and increased significantly with increasing total and cancellous bone density. The success rate of OMI did not correlate significantly with cortical bone density. No correlation was found between the six self-drilling micro-implant diameters and torque values. Screw tightening speed had no significant effect on peak torque values, but 6 mm OMI was shown to have significantly higher torque values ​​than 8 mm and 10 mm OMI. Some investigators have reported the effectiveness of using radiographic templates and film holders to create a surgical template for OMI insertion. The success rate of OMI increased significantly with increasing OMI length and placement height, as well as with decreasing angle. Conclusions. Considering the study’s results, it can be concluded that the success of micro implants includes factors related to the patient, the orthodontist, and the design and material of these devices. Due to their numerous advantages, micro implants should be widely used in modern orthodontic practice for the treatment of all possible occlusion pathologies. The proposed methods for measuring the diagonal dimensions of dental arches are based on the position of the interdental point, which can change its position in case of anomalies in the shape and size of dental arches. That is why optimizing methods for determining the shape and size of dental arches, considering the individual characteristics of the maxillofacial region within the framework of modern orthodontic diagnostics, requires a more in-depth and detailed study to improve diagnostic and therapeutic measures.